(untitled) (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The experiment was carried out at Agronomy Field laboratory, Department of Agronomy and Agricultural Extension, university of Rajshahi, to study the effect of irrigation and sowing method on yield and yield attributes of mustard. The experiment consists of two factors i) irrigation viz. no irrigation (I0), one irrigation (I1)and two irrigations (I2) ii) sowing method viz. line sowing method (M1) and broadcasting method (M2). A split- plot design was used for the experiment by assigning the irrigation on the main plots and sowing method to the sub plots with three replications. Irrigation had significant effect on all the yield and yield contributing characters. The highest plant height, number of branches plant-1, filled siliqua plant-1, sliqua length, number of seed siliqua-1, 1000-seed weight and stover yield were obtained from I2 (two irrigations) and consequently it produced the highest seed yield. Sowing method also had significant influence on almost all the yield and yield contributing characters. All the yield contributing characters except number of unfilled siliqua plant-1were found best at line sowing method (M1) and consequently it produced the highest seed yield. However it could be noted from the study that the combination of two irrigations with line sowing method is better to get higher yield of mustard.